INDIAN CULTURAL HERITAGE - RAJASTHANI FOLK MUSIC: भारतीय सांस्कृतिक विरासत- राजस्थानी लोक संगीत - Kale, Malini (International Journal of Research -GRANTHAALAYAH, 2015)
Indian music is the foundation of music. Indian lifestyle is inspired by music itself. With the creation of the universe, there is no page of human scripture that is void of music. As soon as he was born, the music that he heard was composed in his heart for life, and eventually he remained very close to the end of this music. This music is a form of protection of human body. भारतीय संगीत का मूलाधार संगीत है। संगीत से ही भारतीय जीवन शैली अनुप्रेरित है। सृष्टि के निर्माण से मानव के ग्रंथ का कोई भी पृष्ठ ऐसा नहीं है जो संगीत से शून्य हो। जन्म लेते ही जो गीत सुने उसका संगीत जीवन पर्यन्त रग रग में रचता गया और अन्ततः इसी संगीत के अंतिम काल तक उसका सान्निध्य रहा। यह संगीत मानव शरीर की सŸाा का स्वरूप है।